Genetic surveillance of Plasmodium falciparum populations following treatment policy revisions in the Greater Mekong Subregion - Varanya Wasakul; Tess D. Verschuuren; Nguyen Thuy-Nhien; Ethan Booth; Huynh Hong Quang; Ngo Duc Thang; Keobouphaphone Chindavongsa; Siv Sovannaroth; Virasak Banouvong; Viengphone Sengsavath; Mayfong Mayxay; Nguyen Thi Kim Tuyen; et al. (Nature Communications)
Abstract Genetic surveillance of Plasmodium falciparum (Pf) can track antimalarial-resistant strains, to inform decision-making by National Malaria Control Programmes (NMCPs). The GenRe-Mekong project prospectively collected 5982 samples in the Greater Mekong Subregion (GMS) between 2017 and 2022, genotyping drug resistance markers, and barcodes that recapitulate genetic variation. Genotypes were analyzed with the grcMalaria R package, first described in this paper, to translate genetic epidemiology data into actionable visual information. Since 2020, Pf incidences decreased rapidly, accompanied by a decline of dihydroartemisinin-piperaquine (DHA-PPQ) resistant lineages, previously dominant in the eastern GMS. The frequency of plasmepsin2/3 amplifications, conferring piperaquine resistance, dropped from 62% in 2017-2019 to 2% in 2022, coinciding with a switch in frontline therapy in Cambodia, Thailand, and Vietnam. While regional artemisinin resistance levels remained high, no evidence of emerging mefloquine resistance was found. Routine genetic surveillance proved valuable in monitoring rapid parasite population changes in response to public health interventions, providing actionable information for NMCPs.